Numerical Analysis on Uncoordinated Deformation in Highway Subgrade Widening. Issue 7 (April 2020) - Tang, Lanjun
Abstract: Finite element model of widened subgrade by finite element analysis software is established. The uncoordinated deformation rule of the subgrade widening is studied. By considering the different heights of embankment, different excavated slope, uncoordinated deformation is comparably analyzed. It is resulted that the uncoordinated deformation of the high filling subgrade widening is greater than the one of low embankment widening. The stepper original subgrade excavated slope is, the larger deformation will be on the foundation and subgrade. And uncoordinated deformation is more obvious. Moreover, ground settlement is bottomed at the old road center and it increased with distance away from it. Also, the uncoordinated deformation peaked at the original toe.